Association between xylem vasculature size and freezing survival in winter barley. (1st August 2021) - Tamang, Bishal G.; López, José R.; McCoy, Erik; Haaning, Allison; Sallam, Ahmad; Steffenson, Brian J.; Muehlbauer, Gary J.; Smith, Kevin P.; Sadok, Walid
Abstract: Winter survival is a major yield‐limiting factor in winter barley grown in the Upper Midwest, where winter temperatures regularly reach −20°C or lower. Here, we tested the hypothesis that improved freezing survival is associated with smaller xylem vessel diameters as a mechanism that minimizes physical damage arising from intracellular ice formation, using leaf vasculature as a proxy trait. A second goal was to test whether such anatomical differences could be captured non‐destructively via gas exchange measurements. We first identified a group of 11 winter barley genotypes that exhibited differential field winter survival. We then conducted xylem diameter measurements on the first three leaves on all genotypes in two independent experiments based on 1, 188 images, in addition to leaf gas exchange measurements. Freezing‐tolerant genotypes consistently exhibited significantly smaller metaxylem vessel diameters irrespective of leaf rank, and this difference was not influenced by hardening, indicating that this trait is heritable. Additionally, genotypes with smaller vasculature tended to exhibit lower stomatal conductance and transpiration rates. Our data indicate that genotypes with leaf xylem diameters smaller than 30 µ m are prime donor parents and could be identified using gas exchange measurements, pointing to new phenotyping approaches to accelerate breeding for freezing survival.